2011
DOI: 10.1155/2011/109280
|View full text |Cite
|
Sign up to set email alerts
|

Glufosinate Effects on Nitrogen Nutrition, Growth, Yield, and Seed Composition in Glufosinate-Resistant and Glufosinate-Sensitive Soybean

Abstract: Glufosinate applied to glufosinate-resistant crops may drift and injure glufosinate-sensitive crops. A 2-yr field study examined glufosinate effects on plant injury, chlorophyll content, nodulation, nitrogenase activity, leaf nitrogen, yield, and seed composition in soybean. Glufosinate drift was simulated by application at 45 g/ha to glyphosate-resistant and conventional (glufosinatesensitive) soybean at 3 weeks after planting (WAP). Glufosinate effects were also evaluated in glufosinate-resistant soybean at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…PPT caused a decrease in chlorophyll content in non-transgenic soybean plants three days after treatment [49]. In non-transgenic birch saplings, three days after treatment with the 0.5% PPT solution, the chlorophyll A and carotenoids content significantly decreased, after the 1% solution the total of chlorophyll A and B also decreased, and after treatment with the 2% solution the same happened to chlorophyll B.…”
Section: Discussionmentioning
confidence: 88%
“…PPT caused a decrease in chlorophyll content in non-transgenic soybean plants three days after treatment [49]. In non-transgenic birch saplings, three days after treatment with the 0.5% PPT solution, the chlorophyll A and carotenoids content significantly decreased, after the 1% solution the total of chlorophyll A and B also decreased, and after treatment with the 2% solution the same happened to chlorophyll B.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, other studies do not even report injury symptoms for the application of glufosinate (Barnes et al 2017;Chahal and Jhala 2015;Jhala et al 2017;Landry et al 2016). Reddy et al (2011) observed changes in the composition of LL soybean seeds under two applications of glufosinate (450 and 450 g ha −1 at the V3 and V6 stages, respectively). Glufosinate increased the protein concentration and decreased the oil concentration compared with the treatment without application.…”
Section: Glufosinate Rates In Two Ll Soybean Cultivars (With the Pat mentioning
confidence: 85%
“…In glufosinate-tolerant rice, the strength and germination of the seeds submitted to the glufosinate application did not decrease (Webster et al, 2003). Moreover, in glufosinate-tolerant soybean, applications of the herbicide increased the protein content and diminished the oil and linoleic acid content of the seeds (Reddy et al, 2011).…”
Section: Resultsmentioning
confidence: 87%